Mission accomplished? A scoping review and bibliometric analysis of the term "planetary health" in the peer-reviewed literature. (September 2019) - Rossa-Roccor, Verena; Acheson, Emily; Andrade-Rivas, Federico; Coombe, Michelle; Ogura, Saori; Super, Laura; Hong, Andy
Abstract: Background: Planetary health is an emerging holistic health field that aims to disrupt the boundaries of unidisciplinary research by fostering collaborations, integrating Indigenous knowledge, facilitating education, and driving public and policy engagement. To understand to what degree the field has been successful in meeting this mandate, we conducted a scoping review and bibliometric analysis of the term "planetary health" in the peer-reviewed literature. Methods: An interdisciplinary research team conducted a systematic literature search in 14 databases. The search strategy examined the years 2005–18 with the term "planetary health" in title, abstract, or keywords; no limitations were used regarding language or geographical location. Search results were sorted into three different categories: commentaries, education, and original research. Results in the latter were categorised under the themes suggested by the Planetary Health Alliance. Obtained bibliographic data were analysed with the R bibliometrix package. Findings: Our inclusion criteria identified 180 articles. Preliminary analysis showed that most publications (n=153, 85%) were commentaries, calls to action or framework suggestions. 12 publications reported on educational content and 15 publications reported original research. The themes "nutrition" and "changing food systems" were most commonly discussed in the research papers while "urbanization" and "changing biochemical flows" were not discussed. Ten publications considered Indigenous knowledge and traditions. The number of publications remained low until 2014 but has tripled since 2017. The USA was the most productive country (32%), followed by the UK (16%), and Australia (9%). The most common keyword was "climate change", followed by "public health". Interpretation: Planetary health aims to bridge the gaps both between academic fields and beyond academia. However, based on the results of this study, the term is currently mostly used in commentary-like publications. We need to "spread the word" to better connect researchers, academic fields, and efforts worldwide and under the planetary health umbrella. Funding: None.